2019
DOI: 10.1590/s0102-865020190010000001
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study of exenatide effects on renal injury in diabetic rats

Abstract: Purpose To investigate the effects of exenatide on renal injury in streptozotocin-induced diabetic rats. Methods Fifty SD rats were randomly divided into normal control, model, exenatide-1, exenatide-2 and exenatide-3 groups, 10 rats in each group. The diabetic nephropathy model was constructed in later 4 groups. Then, the later 3 groups were treated with 2, 4 and 8 μg/kg exenatide for 8 weeks, respectively. The serum and urine biochemical indexes and oxidative stress a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…Zitman-Gal et al revealed that liraglutide attenuated the phosphorylation of JAK2 and STAT3 in AGE-stimulated endothelial cells and the kidney of db/db mice ( Zitman-Gal et al., 2019 ). Furthermore, it has been reported that the administration of exenatide attenuates the renal inflammation index, including reducing the TNF-α, IL-6, hsCRP, and CCL5 levels, in STZ-induced diabetic rats by increasing the superoxide dismutase and decreasing malondialdehyde levels ( Wang et al., 2019 ). Taken together, the prevention of oxidative stress and inflammation is a key mechanism for the renoprotective effects of GLP-1RAs.…”
Section: Renoprotective Mechanisms Of Glp-1rasmentioning
confidence: 99%
“…Zitman-Gal et al revealed that liraglutide attenuated the phosphorylation of JAK2 and STAT3 in AGE-stimulated endothelial cells and the kidney of db/db mice ( Zitman-Gal et al., 2019 ). Furthermore, it has been reported that the administration of exenatide attenuates the renal inflammation index, including reducing the TNF-α, IL-6, hsCRP, and CCL5 levels, in STZ-induced diabetic rats by increasing the superoxide dismutase and decreasing malondialdehyde levels ( Wang et al., 2019 ). Taken together, the prevention of oxidative stress and inflammation is a key mechanism for the renoprotective effects of GLP-1RAs.…”
Section: Renoprotective Mechanisms Of Glp-1rasmentioning
confidence: 99%
“…SOD is a crucial enzyme widely existing in the body. Its content can mirror free radicals scavenging ability [ 63 ]. The SOD could be postulated as the start of sparks for antioxidant cascade by superoxide anion detoxification into hydrogen peroxide [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Liang et al in 2020 provided further direct evidences indicating liraglutide protects against diabetic nephropathy by downregulation of TXNIP (thioredoxin-interacting protein), which acts as an oxidative stress inducer in male high fed diet mice [ 46 ]. Similarly, Wang and coworkers reported that exenatide exerts renoprotective effects by suppressing oxidative damage in diabetic rats [ 47 ]. Therefore, it has been hypothesized that improvement of renal function and reduction in albuminuria might be associated with the antioxidant properties of these agents [ 48 50 ].…”
Section: Renoprotective Effects Of Glp-1r Agonistsmentioning
confidence: 99%
“…More recently, Cappetta and colleagues showed that DPP-4 inhibition might reduce the progression of DN by suppressing the inflammatory mediators, such as TNF- α , IL-1 β , IL-6, and MCP-1 in rats [ 57 ], suggesting a potential immunomodulatory effect for these drugs. In addition, Wang and colleagues in 2019 reported that exenatide provided protective effects against DN via alleviating the inflammatory responses in diabetic rats [ 47 ]. They found that exenatide reduced inflammatory markers such as TNF- α , IL-6, CRP, and CCL-5 (chemokine C-C motif ligand 5) in renal tissues [ 47 ].…”
Section: Renoprotective Effects Of Glp-1r Agonistsmentioning
confidence: 99%
See 1 more Smart Citation